2018
DOI: 10.2169/internalmedicine.9246-17
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Pleural Mesothelioma with Bone Marrow Metastases

Abstract: A 64-year-old man with the bone marrow metastasis due to malignant pleural mesothelioma (MPM) was diagnosed with anemia, leukoerythroblastosis, thrombocytopenia, and lower back pain. A bone marrow biopsy demonstrated infiltrative malignant mesothelioma lesions in the bone marrow. The patient died within 15 days of the detection of the bone marrow involvement. Physicians should consider performing a bone marrow biopsy to diagnose bone marrow metastasis and treat patients with palliative chemotherapy at an earli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…MPM is generally considered a locally invasive tumor, and bone marrow metastasis from MPM is considered an extremely rare consequence ( 5 ). One study of postmortem records of 318 patients with MPM revealed that tumors were detected in extrathoracic organs in 55.4% of the cases, and almost all organs were involved including the liver (31.9%), spleen (10.8%), thyroid (6.9%), and brain (3.0%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MPM is generally considered a locally invasive tumor, and bone marrow metastasis from MPM is considered an extremely rare consequence ( 5 ). One study of postmortem records of 318 patients with MPM revealed that tumors were detected in extrathoracic organs in 55.4% of the cases, and almost all organs were involved including the liver (31.9%), spleen (10.8%), thyroid (6.9%), and brain (3.0%).…”
Section: Discussionmentioning
confidence: 99%
“…Metastasis to the bone marrow most commonly arises from prostate, breast, and lung cancers and neuroblastoma ( 4 ). In contrast, bone marrow metastasis due to MPM is very rare ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Immunotherapy of MESO exhibits satisfactory clinical outcomes as well [ 12 ]. Bone metastasis is a rare but much more serious feature in MESO [ 13 , 14 ]. Hence, it is of high clinical significance to elucidate immune-related molecular mechanisms that are associated with MESO bone metastasis, which will aid in the amelioration of individualized therapeutic methods for advanced patients.…”
Section: Introductionmentioning
confidence: 99%